Lombok Islamic Tourism Attractiveness: Non-Moslem Perspectives - Bastaman, Aam - (International Journal of Supply Chain Management, 2018)
Regional Government of Lombok, West Nusa Tenggara (previously known as Lesser Sunda Islands) has declared the island of Lombok as Islamic tourism destination. The aim is to keep Islamic tradition in Lombok and offer Lombok uniqueness with strong Islamic characteristics and background to visitors. This new Islamic branding also to differentiate Lombok with Bali which is perceived too western, despite its strong local culture. The Islamic tourism branding is also to attract Moslem visitors from both local and overseas as well non-Moslem to enjoy Lombok without having to leave Islamic way of life and for the host on welcoming and serving the tourists during the visit. This new branding however arises some new questions; how the non-Moslem would response to the new Islamic tourism branding and what are the related potential issues and concerns. To answer the questions a preliminary qualitative study was conducted  through series of interview with some Indonesian non-Moslem informants who have strong interest in tourism. The result suggest there is an acceptenace of Islamic tourism and branding and signifies Indonesia as Moslim country. Peace, inclusiveness, and being universal are the potiential key branding points for Islamic tourism in Lombok, with the island natural beauty and cultural heritage as the main attraction. however, there is a concern of misunderstanding of Islam as religion which emphasizes on strictnes and restrictions. Yet the issue could further be explored in the future research.